2015
DOI: 10.1007/s11295-015-0904-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic diversity and differentiation in resistance gene clusters of two hybridizing European Populus species

Abstract: Resistance genes (R-genes) are essential for longlived organisms such as forest trees, which are exposed to diverse herbivores and pathogens. In short-lived model species, R-genes have been shown to be involved in species isolation. Here, we studied more than 400 trees from two natural hybrid zones of the European Populus species Populus alba and Populus tremula for microsatellite markers located in three R-gene clusters, including one cluster situated in the incipient sex chromosome region. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…In the case of plant R-genesand immune system genes more generallynegative frequency dependence leading to balancing selection can maintain alleles in gene pools for a range of different timescales (Bakker et al 2006;Charlesworth 2006;Bomblies & Weigel 2007), likely including trans-species polymorphisms. We note that most of the NBS-LRRs under long-term positive selection in our study exhibited significantly increased nucleotide diversity compared with genomewide expectations (Table S8, Supporting Information) and that balancing selection has previously been detected for markers tagging NBS-LRR genes in these species (Caseys et al 2015b Speciation with recurrent gene flow: an intrinsic consequence of adaptive divergence?…”
Section: Genomic Footprints Of Selectionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the case of plant R-genesand immune system genes more generallynegative frequency dependence leading to balancing selection can maintain alleles in gene pools for a range of different timescales (Bakker et al 2006;Charlesworth 2006;Bomblies & Weigel 2007), likely including trans-species polymorphisms. We note that most of the NBS-LRRs under long-term positive selection in our study exhibited significantly increased nucleotide diversity compared with genomewide expectations (Table S8, Supporting Information) and that balancing selection has previously been detected for markers tagging NBS-LRR genes in these species (Caseys et al 2015b Speciation with recurrent gene flow: an intrinsic consequence of adaptive divergence?…”
Section: Genomic Footprints Of Selectionsupporting
confidence: 54%
“…We note that most of the NBS‐LRRs under long‐term positive selection in our study exhibited significantly increased nucleotide diversity compared with genomewide expectations (Table S8, Supporting Information) and that balancing selection has previously been detected for markers tagging NBS‐LRR genes in these species (Caseys et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In the wpa-19 region, a cluster of 14 genes coding for TIR-NB-LRR disease resistance proteins genes was identified. Several works revealed the presence on chromosome 19 of disease resistance genes and resistant phenotypes because many of the poplar NB-LRR genes (more than 70,) are gathered into a supercluster localized on that chromosome [ 54 ]. The largest NB–LRR gene supercluster on Populus chromosome 19 co-localized with the resistance loci MER, R1, and RUS,.…”
Section: Discussionmentioning
confidence: 99%
“…We used analyses of genomic clines implemented in bgc (Gompert & Buerkle, 2012) to study patterns of introgression in hybrids and identify genomic regions that resist introgression due to selection. This genomic cline approach has been used in several recent studies to explore patterns of introgression in hybrids (e.g., Caseys, Stölting, Barbará, González-Martínez, & Lexer, 2015;Gompert et al, 2012a;Janousek et al, 2012;Nosil et al, 2012;Parchman et al, 2013;Trier, Hermansen, Saetre, & Bailey, 2014), and simulations have demonstrated that it is robust to the detection of loci with clines that deviate from the genomewide expectation (Gompert & Buerkle, 2011). Finally, to explore potential selective pressures driving patterns of divergence and introgression, we test the hypothesis that a priori sets of candidate genes are enriched for outlier loci ( Figure 1b).…”
Section: Introductionmentioning
confidence: 99%